2021
DOI: 10.3390/metabo11080479
|View full text |Cite
|
Sign up to set email alerts
|

Fructose and Mannose in Inborn Errors of Metabolism and Cancer

Abstract: History suggests that tasteful properties of sugar have been domesticated as far back as 8000 BCE. With origins in New Guinea, the cultivation of sugar quickly spread over centuries of conquest and trade. The product, which quickly integrated into common foods and onto kitchen tables, is sucrose, which is made up of glucose and fructose dimers. While sugar is commonly associated with flavor, there is a myriad of biochemical properties that explain how sugars as biological molecules function in physiological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 136 publications
2
8
0
Order By: Relevance
“…Since the observed number of differential genes in the rumen and ileum was small (Supplementary file 4), a further GSEA was conducted to detect subtle gene expression changes. Fructose and mannose metabolisms are vital in cellular productivity, complex cellular processes (e.g., glycosylation) and cellular health (Lieu et al, 2021). In the present study, the GSEA analysis showed that feeding silybum marianum meal to growing lambs upregulated some genes in the fructose and mannose metabolism pathway in the rumen.…”
Section: A B Figuresupporting
confidence: 53%
“…Since the observed number of differential genes in the rumen and ileum was small (Supplementary file 4), a further GSEA was conducted to detect subtle gene expression changes. Fructose and mannose metabolisms are vital in cellular productivity, complex cellular processes (e.g., glycosylation) and cellular health (Lieu et al, 2021). In the present study, the GSEA analysis showed that feeding silybum marianum meal to growing lambs upregulated some genes in the fructose and mannose metabolism pathway in the rumen.…”
Section: A B Figuresupporting
confidence: 53%
“…Osmolytes, such as sucrose, fructose, and mannose, are resources of energy, nutrition, structural materials, signaling molecules, and crucially contribute to seed germination and the growth of plantlets ( Osuna et al, 2015 ). Maize ( Zea mays L.) seedlings exposed to heat stress displayed sudden degradation of glycan contents and upregulated fructose and mannose metabolism ( Lieu et al, 2021 ). The expression of genes involved in fructose, mannose, and sucrose biosynthesis was also upregulated in 21-day-old maize seedlings exposed to heat stress ( Stavridou et al, 2021 ).…”
Section: Physiological Effects Of Heat Stressmentioning
confidence: 99%
“…RNAi against Mpi (MPI), another gene in the GDP-mannose pathway, worsened the DPAGT1 and ER stress models (S7 Table ). However, MPI interconverts mannose-6-phosphate and fructose-6-phosphate [72], which means its inhibition could increase or decrease GDPmannose synthesis. Given that we also see differential effects of fructose in our two models, metabolomic analysis of these pathways may be required to understand the exact mechanism of Mpi loss under DPAGT1 impairment.…”
Section: Discussionmentioning
confidence: 99%